Extraction of CU(II) from aqueous solutions by palm kernel fatty acid distillate-based bulk liquid membrane/ Siti Fatimah Abdul Halim - Abdul Halim, Siti Fatimah (2021)
This research aimed to explore the feasibility of replacing the traditional petroleum-based organic solvents, which are toxic and non-renewable, with a free fatty acid (FFA)-rich oil as the sole membrane phase of a bulk liquid membrane (BLM) for the simultaneous removal (extraction) and recovery (stripping) of Cu(II) from aqueous solutions. This FFA-rich oil was employed as a reactive organic solvent withoutthe addition of extractant and modifier, which eliminated the use of hazardous chemicals in conventional or green organic solvents. Formic acid (weak organic acid) was used as the stripping agent as it has the advantage in terms of less corrosive and damaging to equipment. The best extraction (type of FFA-rich oils, equilibrium pH (pHeq), organic to aqueous (O:A) ratio, inert salt concentration and temperature) and stripping (type of stripping agents, concentration of stripping agent and O:A ratio) conditions were first determined by solvent extraction, followed by an investigation of the design and operating parameters for a BLM. The solvent extraction results revealed that palm kernel fatty acid distillate (PKFAD) was the most suitable FFA-rich oil for Cu(II) extraction, while formic acid was the best stripping agent for Cu(II) stripping from loaded PKFAD. The highest Cu(II) extraction of 98% was achieved at pHeq of 4.7, O:A ratio of 0.5:1, an inert salt concentration of 200 mM, and a temperature of 25 °C, while a high Cu(II) stripping from Cu(II)-loaded PKFAD of 94% was accomplished with 1 M formic acid at O:A ratio of 1:1. Under these extraction and stripping conditions, the estimated loading capacity and reusability of PKFAD were 7520 mg/L and more than 15 consecutive extraction-stripping cycles, respectively. Both the equilibrium slope and numerical analysis revealed that the stoichiometry of Cu(II)-FFA complexes (extracted species) in PKFAD was 1:6, whereas the thermodynamic study indicated that Cu(II) extraction by PKFAD was exothermic, enthalpy-driven, and non-spontaneous over the temperature range studied. A plausible structure (outer-sphere) of the Cu(II)-FFA complexes in PKFAD was also predicted from the thermodynamic data obtained. The suitable design parameters (4 impeller blades and without baffles) for a PKFAD-based BLM were then selected and its operating parameters (stirring speed of 220 rpm, buffer concentration of 0.2 M, and reaction time of 7 hours) were investigated for the maximum overall recovery of Cu(II). The rate-controlling steps of both extraction (diffusion-controlled) and stripping (intermediate-controlled) processes in the PKFAD-based BLM were determined and a facilitated counter-coupled transport mechanism was proposed. A comparison of the kinetic parameters between the PKFAD- and lauric acid (LA)-based BLM systems revealed that the variation in the kinetics parameter is due to the different extractants and diluents used. While mixed FFA and diluents are used in the PKFAD- based BLM system, a single extractant (LA) and diluent (diethyl-ethylene) is used in the LA-based BLM system. The PKFAD-based BLM was also capable of recovering Cu(II) (82%) from a real electroplating influent solution containing mixed anions (chloride, nitrate, sulfate and cyanide) and cations (sodium, potassium, nickel, cobalt and chromium).